El tiempo libre en el cumplimiento de las tareas escolares de los niños y niñas del 6to y 7mo año de educación básica de la escuela “Fray Vicente Solano”, del Cantón Chillanes, provincia Bolívar, período lectivo 2011 – 2012 - Barros Arteaga, Lorena Del Rocio (2012)
In this work the fundamental necessity is considered to know how to take advantage of the free time suitably, especially in cumplimient of the scholastic tasks; with the purpose of improving the academic yield of the students of the school; that one as well constitutes in the base for the improvement of the quality and the education. For the effect, the work is developed in several chapters; in his first part is the subject, the antecedents, the problem, the justification, objective, general as as much specific, hypothesis, variables and the operacionalización of variables. In the first chapter the theoretical fundamentation of the work, constituted by the scientific theory is sintetizada, in that the two variables are developed, the one that it concerns to the advantage of free time, his characteristics, importance and utility; as well as the fulfillment of the scholastic tasks, that are due to obtain with the children and children of the school. The second chapter talks about to the applied methodologic strategies for the development of the work, where the types of investigation are considered, the universe and shows to be investigated, as well as the methods for the work and the techniques for the investigation. In which it concerns to the third chapter, there the analysis of the results obtained through the investigation of field is carried out; with results organized in the statistical table, and represented in the bar charts, and foot it is the analysis of each carried out question to the students of the Fray school Vicente Solano. The fourth chapter, is the one that contains the proposal, like an alternative with which it looks for to solve the problem detected through the investigation and that in our case, talk about strategies to take advantage of the free time